Robert Frost and the New England Renaissance - Monteiro, George (Book collections on Project MUSE., 2015)
""A poem is best read in the light of all the other poems ever written."" So said Robert Frost in instructing readers on how to achieve poetic literacy. George Monteiro's newest book follows that dictum to enhance our understanding of Frost's most valuable poems by demonstrating the ways in which they circulate among the constellations of great poems and essays of the New England Renaissance. Monteiro reads Frost's own poetry not against ""all the other poems ever written"" but in the light of poems and essays by his precursors, particularly Emerson, Thoreau, and Dickinson. Familiar poems such.